2020
DOI: 10.3389/fpsyg.2020.01014
|View full text |Cite
|
Sign up to set email alerts
|

The Early Elementary School Abbreviated Math Anxiety Scale (the EES-AMAS): A New Adapted Version of the AMAS to Measure Math Anxiety in Young Children

Abstract: Primi et al. The Early Elementary School-AMAS We have also demonstrated the equivalence of the scale across languages (Italian and English). Overall, the findings confirmed the validity and reliability of the new scale in assessing the early signs of math anxiety and in measuring differences between genders and educational contexts. We have also shown that MA was already related to math performance, and teacher's ratings of children's math ability at this young age. Additionally, we have found no gender differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 69 publications
(124 reference statements)
4
36
0
5
Order By: Relevance
“…So is this Philipp (2007) , and the same belief is shared by students in terms of mathematics ( Bermejo et al, 2000a ). As some researchers have shown, there is a consistent relationship between math anxiety and performance (a medium to weak range, from −0.11 to −0.36), and they observe that those students who show higher in levels of MA tend to show poorer mathematics performance ( Primi et al, 2020 ). None of these aspects are facilitators in the teaching-learning process.…”
Section: Constructivist Intervention Programsmentioning
confidence: 94%
“…So is this Philipp (2007) , and the same belief is shared by students in terms of mathematics ( Bermejo et al, 2000a ). As some researchers have shown, there is a consistent relationship between math anxiety and performance (a medium to weak range, from −0.11 to −0.36), and they observe that those students who show higher in levels of MA tend to show poorer mathematics performance ( Primi et al, 2020 ). None of these aspects are facilitators in the teaching-learning process.…”
Section: Constructivist Intervention Programsmentioning
confidence: 94%
“…While cross-sectional studies have consistently found a negative relation between MA-A and children's mathematics performance (e.g., Caviola et al, 2017;Primi et al, 2020;Van Mier et al, 2018), even after controlling for other types of anxiety (e.g., trait anxiety) and cognitive factors (i.e., IQ, working memory) (Lauer et al, 2018;Wu et al, 2012Wu et al, , 2014, this is not the case for studies focusing on the MA-C only (e.g., Dowker et al, 2012Dowker et al, , 2019Haase et al, 2012;Wood et al, 2012). Then again, studies with measures of MA-Com also report a negative relation between MA and mathematics performance (Harari et al, 2013;Jameson, 2013;Kucian et al, 2018).…”
Section: The Relation Between Mathematics Anxiety and Mathematics Performancementioning
confidence: 99%
“…Among younger children, the findings on the negative connection between MA and mathematics performance are less clear, and the role of numerical magnitude processing in this context is virtually unexplored. Some studies, mainly cross-sectional, demonstrate the presence of MA already in early grades (although see Szczygieł & Pieronkiewicz, 2021) and its coupling with inferior mathematics performance (e.g., Cargnelutti et al, 2017;Gunderson et al, 2018;Primi et al, 2020), while other studies have failed to detect this negative connection (Krinzinger et al, 2009;Wood et al, 2012). This also applies to the linkage between MA and numerical magnitude processing.…”
Section: Introductionmentioning
confidence: 99%
“…Other scales have been designed or modified for specific child and adolescent populations, e.g. the Mathematics Anxiety Rating Scale for Adolescents (Suinn & Edwards, 1982), the MARS for Elementary school children (Suinn et al 1988), the Mathematics Anxiety Questionnaire (Wigfield & Meece, 1988), the Mathematics Anxiety Scale for Children (Chiu & Henry, 1990), the Maths Attitude and Anxiety Questionnaire (Dowker et al 2012), the Scale for Early Mathematics Anxiety (Wu et al 2012), the Child Mathematics Anxiety Questionnaire (Ramirez et al 2013), Math Anxiety Scale for Young Children (Harari et al 2013), the Children's Mathematics Anxiety Scale -UK (Petronzi et al 2018), the Modified Abbreviated Math Anxiety Scale (Carey et al 2017), and the Early Elementary School Abbreviated Math Anxiety Scale (Primi et al 2020).…”
Section: Introductionmentioning
confidence: 99%